Characterization of the large‐scale Japanese patient‐derived xenograft (J‐PDX) library. Issue 6 (4th June 2021) - Yagishita, Shigehiro; Kato, Ken; Takahashi, Mami; Imai, Toshio; Yatabe, Yasushi; Kuwata, Takeshi; Suzuki, Mikiko; Ochiai, Atsushi; Ohtsu, Atsushi; Shimada, Kazuaki; Nishida, Toshirou; Hamada, Akinobu; et al.
Abstract: The use of patient‐derived xenografts (PDXs) has recently attracted attention as a drug discovery platform with a high predictive clinical efficacy and a preserved tumor heterogeneity. Given the racial differences in genetic variations, it would be desirable to establish a PDX library from Japanese cancer patients on a large scale. We thus tried to construct the Japanese PDX (J‐PDX) library with a detailed clinical information for further clinical utilization. Between August 2018 and May 2020, a total of 1126 cancer specimens from 1079 patients were obtained at the National Cancer Center Hospital and National Cancer Center Hospital East, Japan, and were immediately transplanted to immunodeficient mice at the National Cancer Center Research Institute. A total of 298 cross‐cancer PDXs were successfully established. The time to engraftment varied greatly by cancer subtypes, especially in the first passage. The engraftment rate was strongly affected by the clinical stage and survival time of the original patients. Approximately 1 year was needed from tumor collection to the time when coclinical trials were conducted to test the clinical utility. The 1‐year survival rates of the patients who were involved in establishing the PDX differed significantly, from 95.6% for colorectal cancer to 56.3% for lung cancer. The J‐PDX library consisting of a wide range of cancer subtypes has been successfully established as a platform for drug discovery and development in Japan. When conducting coclinical trials, it is necessary to consider the target cancer type, stage, and engraftment rate in light of this report. Abstract : We have successfully established a PDX library derived from Japanese cancer patients. In less than 2 years, we have registered more than 1000 specimens and established nearly 300 PDXs. We will further enrich the library and use it as a platform to accelerate drug discovery in Japan.